Numerical simulations of 2-DOF vortex-induced vibration of a circular cylinder in two and three dimensions: A comparison study - Xuepeng Fu; Shixiao Fu; Zhaolong Han; Zhibo Niu; Mengmeng Zhang; Bing Zhao (Journal of Ocean Engineering and Science, 2025)
Finding a reliable and efficient numerical method is of great importance for the safety design of a offshore riser whose model can be simplified as vortex-induced vibration (VIV) of an elastically-mounted circular cylinder. In the current study, two-degree-of-freedom (2-DOF) VIV responses of a circular cylinder with a small mass ratio m*=2.6 and small mass damping parameter (m*+1)ζ=0.013 is numerically investigated by two- and three-dimensional method. The simulations by using the URANS (Unsteady Reynolds Averaged Navier-Stokes) in combination with the SST (Shear Stress Transport) k−ω turbulence model are performed at subcritical Reynolds numbers (Re ranges from 1×103 to 1.5×104). From the overall results, both the 2D and 3D simulations can obtain relatively accurate statistical results including VIV response amplitudes and frequency values. The main differences between the 2D and 3D simulations lie on the three-dimensional effects that exist in the supper upper branch and the flow transition condition. However, the 2D numerical simulations can save hundreds of times of the computational resources compared with a 3D simulation, hence is more suitable for engineering VIV prediction under such conditions. The comparison of simulation and experimental results in this study provides research support for the selection of appropriate simulation methods (2D or 3D) for 2-DOF VIV of an offshore riser in research and engineering.